1990
DOI: 10.1111/j.1349-7006.1990.tb02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antitumor Activity and Intestinal Toxicity of 5′‐Deoxy‐5‐fluorouridine and Its Prodrug Trimethoxybenzoyl‐5′‐deoxy‐5‐fluorocytidine

Abstract: N4-Trimethoxybenzoyl-5'-deoxy-5-fluorocytidine (Ro 09-1390), a prodrug of the cytostatic 5'-deoxy-5-fluorouridine (5'-DFUR), was synthesized with the aim of reducing of the dose-limiting toxicity of 5'-DFUR, which is diarrhea. In mice bearing Lewis lung carcinoma, 5'-DFUR given po produced a substantial amount of 5-fluorouracil (5-FU) in the intestinal tract as well as tumors, where the enzyme pyrimidine nucleoside phosphorylase, essential for conversion of 5'-DFUR to 5-FU, is predominantly located. With the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Therefore, CAP activation appears to be blocked at the cytidine deaminase step. This confirms the low cytidine deaminase activity in rat liver (Camenier and Smith, 1965) and suggests a lack of an extra-hepatic cytidine deaminase activity in rat in agreement with previous studies on other 5Ј-DFCR-related compounds such as galocitabine (Ninomiya et al, 1990;Funaki et al, 1993). On the contrary, the high activity of cytidine deaminase is revealed by the low value of the 5Ј-DFCR/5Ј-DFUR ratio (Ͻ1) in mice treated with a LD or a HD of CAP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, CAP activation appears to be blocked at the cytidine deaminase step. This confirms the low cytidine deaminase activity in rat liver (Camenier and Smith, 1965) and suggests a lack of an extra-hepatic cytidine deaminase activity in rat in agreement with previous studies on other 5Ј-DFCR-related compounds such as galocitabine (Ninomiya et al, 1990;Funaki et al, 1993). On the contrary, the high activity of cytidine deaminase is revealed by the low value of the 5Ј-DFCR/5Ј-DFUR ratio (Ͻ1) in mice treated with a LD or a HD of CAP.…”
Section: Discussionsupporting
confidence: 91%
“…Since cholestasis has not been described as a side effect of CAP treatment, it is likely that 5Ј-DFCR-G does not affect the physicochemical properties of bile in contrast to what has been observed with a biliary conjugate of FBAL (Sweeny et al, 1987). The third activation step of CAP leads to the formation of 5-FU that occurs mainly via uridine phosphorylase in rodents and thymidine phosphorylase in humans (Ninomiya et al, 1990). FBAL, the main catabolite of 5-FU, is formed since dihydropyrimidine dehydrogenase (E.C.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration requires higher dosages than intravenous injection due to first pass effects. Adverse effects such as diarrhea have been reported following the administration of tegafur or doxifluridine (Ohta et al, 1980;Ninomiya et al, 1990).…”
mentioning
confidence: 99%
“…When galocitabine was given orally to mice, only a small amount of 5-FU was formed in the intestine. On the other hand, when 5'-DFUR was given orally to mice, a substantial amount of 5-FU was produced in the intestine and more severe intestinal toxicity was observed compared with that of galocitabine (Ninomiya et al, 1990). These results suggested that oral 5'-DFUR could be converted to 5-FU at the absorption site by TP; however, galocitabine produced less 5-FU during the absorption process.…”
Section: Figmentioning
confidence: 97%
“…Before the development of capecitabine, galocitabine (trimethoxybenzyl-5'-deoxy-5-fluorocytidine), an acyl-type analog, had been selected as the new fluoropyrimidine candidate (Ninomiya et al, 1990). While it was effectively converted to 5'-DFCR by hepatic enzymes in mice, it was not converted so effectively by hepatic CE in humans.…”
Section: Introductionmentioning
confidence: 99%